Sinergi Antara Moralitas dan Profesionalisme dalam Etika Administrasi Publik di Kota Palangka Raya - Yostin Dios; Delon Delon; Mikel Fernando; Intan Kumalasari (Perspektif Administrasi Publik dan hukum, 2025)
This study examines the synergy between morality and professionalism as foundational components in shaping ethical behavior among civil servants in Palangka Raya City. The research is motivated by persistent ethical issues within local government bureaucracy, despite ongoing reform initiatives that emphasize integrity and accountability in public service. Using a quantitative explanatory survey design, data were collected from civil servants across several regional government institutions and analyzed through multiple linear regression to determine the influence of morality and professionalism on ethical behavior. The findings indicate that both variables significantly contribute to the formation of ethical conduct, with morality demonstrating a slightly stronger influence compared to professionalism, thereby confirming theoretical concepts which argue that ethical public administration requires both personal integrity and professional competence. These results highlight the importance of strengthening institutional ethics programs through character building, competency-based professionalism, and transparent supervisory mechanisms to ensure consistency of ethical behavior across administrative practices. The study also acknowledges methodological limitations related to the exclusive use of quantitative measures, suggesting that future research may integrate qualitative approaches to capture deeper subjective meanings of morality and professionalism within public sector settings.